Experimental study of cold inflow and its effect on draft of chimney - Chi-Ming Chu; Raymond Kwok-How Chu; Md. Mizanur Rahman (WIT Press, 2012)
This paper aims to study the cold air inflow into a natural draft air cooled heat exchanger chimney. In total, seven configurations of experiments were carried out in the prototype natural draft air-cooled heat exchanger model for two different supplied heat loads at approximately 0.75 kW to 1.25 kW to determine the effects of wire mesh screen in the chimney performance. Temperature and velocity were measured for the configurations and heat loads. It was found that the Top-only, Top-and-Middle, and Middle-only installations were able to maintain draft velocities to within 3.0 % of the control experiment draft velocity, in spite of the resistance of the mesh. It was also found that configurations utilising mesh at the bottom had experienced a drop in draft velocity by up to 50% from the Control. The smoke flow visualisation tests clearly proved that cold air inflow phenomenon exist, and can be countered with the installation of wire mesh at the top of the model.